IMPROPER STRUCTURE OF THE NIGERIAN POLICE AND THE QUEST FOR STATE POLICE: LESSONS FROM VIGILANTE SERVICES - ABAH, Norbert C; OFFOR, Frank Ifeanyi (Socialscientia: Journal of Social Sciences and Humanities, 2020)
The quest for the establishment of state police in Nigeria has ascended from pedestrian to national discourse and has no doubt generated a lot of controversy as to the role assigned to the Nigerian police formation by the constitution and the way and manner they have been performing these roles. Consequent upon this, the increasing spate of violence that has been unleashed on the citizens of this nation and the resultant deaths has heightened the clamour for state police in Nigeria. This is as a result of the failure of the centrally controlled police formation in Nigeria to provide the needed security to Nigerians, leaving them at the mercy of criminal elements in the society. It is against this background that almost all the states of the federation established their own security outfits to protect their citizens from incessant attacks. It is on this premise that this paper discusses the reasons why there has been continued call for the establishment of state police in Nigeria. The paper also recommends ways to restructure the Nigerian police for better service delivery.